A crystallography-based investigation of weak interactions for drug design against COVID-19. Issue 12 (22nd March 2021) - Sepay, Nayim; Saha, Pranab Chandra; Shahzadi, Zarrin; Chakraborty, Aratrika; Halder, Umesh Chandra
Abstract : Via analyzing 143 crystal structures of SARS-CoV-2 M pro, we identified the most important active site amino acids, the nature and propensity of their interactions with small molecules and the relevant fragments of ligands to design new pharmacophores. Abstract : Interactions between proteins and small molecules play important roles in the inhibition of protein function. However, a lack of proper knowledge about non-covalent interactions can act as a barrier towards gaining a complete understanding of the factors that control these associations. To find effective molecules for COVID-19 inhibition, we have quantitatively investigated 143 X-ray crystal structures of the SARS-CoV-2 M pro protein of coronavirus with covalently or non-covalently bound small molecules (SMs). Our present study is able to explain ordinary and perceptive aspects relating to protein inhibition. The active site of the protein consists of 21 amino acid residues, but only nine are actively involved in the ligand binding process. The H41, M49, and C145 residues have highest priority with respect to interactions with small molecules through hydrogen bond, CH–π, and van der Waals interactions. At the active site, this ranking of amino acids is clear, based on different spatial orientations of ligands, and consistent with the electronic properties. SMs with aromatic moieties that bind to the active site of the protein play a distinct role in the determination of the following order of interaction frequency with the amino acids: CH–π > H-bonding > polar interactions. This present study revealed that the G143 and C145 residues play crucial roles in the recognition of the carbonyl functionality of SMs through hydrogen bonding. With this knowledge in mind, an effective inhibitor small-molecule for SARS-CoV-2 M pro was designed: docking studies showed that the designed molecule has strong binding affinity towards the protein. The non-covalent interactions in the protein–ligand complex are in good agreement with the results obtained from X-ray crystallography. Moreover, the present study focused on weak forces and their influence on protein inhibition, henceforth shedding much light on the essential requirements for moieties that should be present in a good inhibitor and their orientations at the ligand binding site.